2018
DOI: 10.1007/s10811-017-1387-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased growth response of strawberry roots to a commercial extract from Durvillaea potatorum and Ascophyllum nodosum

Abstract: The withdrawal of soil fumigants like methyl bromide is forcing strawberry growers to consider supplementary and alternative ways of producing crops. In addition to controlling soil-borne pests, soil fumigation causes an increased growth response in strawberry roots, and the use of biostimulants may offer an alternative to replace this response. We tested the hypothesis that treatment with a commercial extract (Seasol®) from the seaweeds Duvillaea potatorum and Ascophyllum nodosum can increase root growth, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 36 publications
7
22
0
2
Order By: Relevance
“…This indicated that seaweeds are efficient bio-fertilizers under normal growth conditions and noticeably increased their plant tolerance under stressful conditions. Khan et al [4] and Mattner et al [33] reported positive outcomes when seaweeds were used. These outcomes included root development, leaf quality, general plant vigor, and resistance to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that seaweeds are efficient bio-fertilizers under normal growth conditions and noticeably increased their plant tolerance under stressful conditions. Khan et al [4] and Mattner et al [33] reported positive outcomes when seaweeds were used. These outcomes included root development, leaf quality, general plant vigor, and resistance to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Different application rates of Kappaphycus alvarezii were investigated in respect to 100% of the recommended dose of fertilizers on maize [29] and potato tubers [30], interestingly, 7.5% was found to be the best application rate at both studies. Similarly, Mattner et al [31] applied a commercial seaweed extract based on Duvillaea potatorum and Ascophyllum nodosum on strawberry at nursery and production stages, results showed an increase of the root length density of plants which had been treated at the production stage regardless of whether the treatment was applied at the nursery stage or not. This increase was highly correlated with the enhancement of the final yield recorded.…”
Section: Overview On the Positive Effect Of Seaweed Extracts On Plantmentioning
confidence: 95%
“…The seaweeds used in this study are different, so the extracts are not identical, therefore we standardized the testing approach. The 1:400 dilution of the extracts were chosen because of (i) greenhouse and field studies demonstrating the efficacy for this dilution ( Mattner et al, 2013 , 2018 ), and (ii) by testing for root growth efficacy using the dilution as described previously ( Arioli et al, 2015 ). For alignment with our previous greenhouse and field studies and the root growth testing, each of the seaweed extracts where standardized to 16% (w/w) soluble solids before preparing the 1 in 400 dilution for each seaweed extract.…”
Section: Methodsmentioning
confidence: 99%
“…This study used the model plant A. thaliana and the generalist, globally devastating pathogen P. cinnamomi, to examine the impacts of treatment of plants with two selected brown algal extract-based biostimulants or their combination, on pathogen growth and development in roots. Several previous studies have shown that applications of various brown algal extracts, either to soil or to foliage, enhanced root growth and plant development (Arioli et al, 2015;Mattner et al, 2018). Here we have used a sand culture system to grow A. thaliana with extracts from A. nodosum ("AN"), or D. potatorum ("DP"), or their combination ("AN/DP").…”
Section: Verification Of the Arabidopsis Thaliana-phytophthora Cinnammentioning
confidence: 99%